Health, social care and technological interventions to improve functional ability of older adults living at home: An evidence and gap map. Issue 3 (7th July 2021) - Welch, Vivian; Mathew, Christine M.; Babelmorad, Panteha; Li, Yanfei; Ghogomu, Elizabeth T.; Borg, Johan; Conde, Monserrat; Kristjansson, Elizabeth; Lyddiatt, Anne; Marcus, Sue; Nickerson, Jason W.; Pottie, Kevin; et al.
Abstract: Background: By 2030, the global population of people older than 60 years is expected to be higher than the number of children under 10 years, resulting in major health and social care system implications worldwide. Without a supportive environment, whether social or built, diminished functional ability may arise in older people. Functional ability comprises an individual's intrinsic capacity and people's interaction with their environment enabling them to be and do what they value. Objectives: This evidence and gap map aims to identify primary studies and systematic reviews of health and social support services as well as assistive devices designed to support functional ability among older adults living at home or in other places of residence. Search Methods: We systematically searched from inception to August 2018 in: MEDLINE, EMBASE, Cochrane Database of Systematic Reviews, CENTRAL, CINAHL, PsycINFO, AgeLine, Campbell Library, ASSIA, Social Science Citation Index and Social Policy & Practice. We conducted a focused search for grey literature and protocols of studies (e.g., ProQuest Theses and Dissertation Global, conference abstract databases, Help Age, PROSPERO, Cochrane and Campbell libraries and ClinicalTrials.gov ). Selection Criteria: Screening and data extraction were performed independently in duplicate according to our intervention and outcome framework. We included completed and on‐going systematic reviews and randomized controlled trials of effectiveness on health and social support services provided at home, assistive products and technology for personal indoor and outdoor mobility and transportation as well as design, construction and building products and technology of buildings for private use such as wheelchairs, and ramps. Data Collection and Analysis: We coded interventions and outcomes, and the number of studies that assessed health inequities across equity factors. We mapped outcomes based on the International Classification of Function, Disability and Health (ICF) adapted categories: intrinsic capacities (body function and structures) and functional abilities (activities). We assessed methodological quality of systematic reviews using the AMSTAR II checklist. Main Results: After de‐duplication, 10, 783 records were screened. The map includes 548 studies (120 systematic reviews and 428 randomized controlled trials). Interventions and outcomes were classified using domains from the International Classification of Function, Disability and Health (ICF) framework. Most systematic reviews ( n  = 71, 59%) were rated low or critically low for methodological quality. The most common interventions were home‐based rehabilitation for older adults ( n  = 276) and home‐based health services for disease prevention ( n  = 233), mostly delivered by visiting healthcare professionals ( n  = 474). There was a relative paucity of studies on personal mobility, building adaptations, family support, personal support and befriending or friendly visits. The most measured intrinsic capacity domains were mental function ( n  = 269) and neuromusculoskeletal function ( n  = 164). The most measured outcomes for functional ability were basic needs ( n  = 277) and mobility ( n  = 160). There were few studies which evaluated outcome domains of social participation, financial security, ability to maintain relationships and communication. There was a lack of studies in low‐ and middle‐income countries (LMICs) and a gap in the assessment of health equity issues. Authors' Conclusions: There is substantial evidence for interventions to promote functional ability in older adults at home including mostly home‐based rehabilitation for older adults and home‐based health services for disease prevention. Remotely delivered home‐based services are of greater importance to policy‐makers and practitioners in the context of the COVID‐19 pandemic. This map of studies published prior to the pandemic provides an initial resource to identify relevant home‐based services which may be of interest for policy‐makers and practitioners, such as home‐based rehabilitation and social support, although these interventions would likely require further adaptation for online delivery during the COVID‐19 pandemic. There is a need to strengthen assessment of social support and mobility interventions and outcomes related to making decisions, building relationships, financial security, and communication in future studies. More studies are needed to assess LMIC contexts and health equity issues.